General Self‐Template Synthesis of Transition‐Metal Oxide and Chalcogenide Mesoporous Nanotubes with Enhanced Electrochemical Performances. (30th May 2016) - Wang, Huan; Zhuo, Sifei; Liang, Yu; Han, Xiling; Zhang, Bin
Abstract: The development of a general strategy for synthesizing hierarchical porous transition‐metal oxide and chalcogenide mesoporous nanotubes, is still highly challenging. Herein we present a facile self‐template strategy to synthesize Co3 O4 mesoporous nanotubes with outstanding performances in both the electrocatalytic oxygen‐evolution reaction (OER) and Li‐ion battery via the thermal‐oxidation‐induced transformation of cheap and easily‐prepared Co‐Asp(cobalt–aspartic acid) nanowires. The initially formed thin layers on the precursor surfaces, oxygen‐induced outward diffusion of interior precursors, the gas release of organic oxidation, and subsequent Kirkendall effect are important for the appearance of the mesoporous nanotubes. This self‐template strategy of low‐cost precursors is found to be a versatile method to prepare other functional mesoporous nanotubes of transition‐metal oxides and chalcogenides, such as NiO, NiCo2 O4, Mn5 O8, CoS2 and CoSe2 .